Gambaran Bimbingan Konseling Pada Fenomena Hustle Culture Dikalangan Mahasiswa, Literatur Review: Description of Guidance Counseling on the Hustle Culture Phenomenon Among Students, Literature Review - Muhammad Agung Budiarjo; Casmini (Sociocouns: Journal of Islamic Guidance and Counseling, 2023)
Hustle Culture is a phenomenon that comes from young people who are motivated by quick success. The Hustle Culture phenomenon has actually been around for a long time, and is now hotly discussed again. The assumption is that this phenomenon, Hustle Culture, is a culture or lifestyle of someone who must prioritize their work or career. With a problem formulation, how is the depiction of Guidance Counseling towards the Hustle Culture phenomenon among students. The data collection method used in library research is secondary data. With the result that guidance and counseling can also influence someone to get out of the Hustle Culture zone. Hustle Culture can be positive and negative where students have to work hard to be successful in their careers and education.